(untitled) (Research, Society and Development, 2020)
The guava usually possesses an intense metabolism during ripening period, presenting an accelerated breathing, inducing at smallest time of life powder-crop of the fruits, visa that is necessary the use of techniques to increase the quality powder-crop. Therefore, it was aimed at to evaluate the influence of coverings with different formulations of cassava starch under the quality powder-crop of the guava ’Paluma’ in two storage conditions. The experiment was accomplished in factorial outline 2x4 (two storage temperatures, one to evaluate the quality of the maintained fruits stored under cooling the (12ºC and 80% UR) and the other under ambient conditions the (25ºC and 60% UR) and four concentrations of cassava starch being them: T1: testifies, without coating; T2: 1% of cassava starch; T3: 2% of cassava starch and T4: 3% cassava starch, with three repetitions and two fruits for portion, for 15 days. For the preparation of the suspensions and application of the coating, they were heavy and diluted, respectively, 10, 20 and 30g of cassava starch in 1 liter of distilled water, being the warm suspensions for 70ºC. The analyzed variables were the loss of fresh mass, the firmness of the fruit, the colorimetry of the fruit, pH, titratable acidity, soluble solids, relationship soluble solids and titratable acidity and ascorbic acid. The use of cassava starch to 2% in ’Paluma’ guava fruits associated to the storage under cooling was efficient, delaying the ripening of the fruits, becoming a promising alternative for the conservation powder-crop of these fruits.